SISTEM INFORMASI INVENTARIS ALAT TULIS KANTOR DAN SUVENIR PADA KANTOR PELAYANAN PAJAK PRATAMA SUMBAWA BESAR BERBASIS DEKSTOP - Mulyanto, Yudi; Satriansyah, Agus; Noviana, Sari (Jurnal TAMBORA, 2019)
This study aims to (1) to design and build an Inventory Information System for Office Stationery and Souvenirs at the Sumbawa Tax Pratama service office, (2) minimize data duplication and faster data retrieval, (3) to facilitate data input and reporting processes. This study uses qualitative data collection methods (observation, documentation and literature study), system design using Unified Modeling Language or UML (use case, activity diagram, sequence diagram and class diagram), the software development method used is waterfall and built using Delphi 7 and databases use Mysql and software testing methods using black boxes, namely testing done by testing the software in terms of functionality. The results of the research are Inventory Information System for Office Stationery and Souvenirs at the Big Sumbawa Large Tax Pratama service office, equipped with a login menu with a different user level, the main menu containing options including ATK and Souvenir, from the menu has a transaction consisting from taking goods, purchasing goods, regional office grants, stock items and reports so as to provide benefits to the Sumbawa Besar Primary Tax Service Pelayanaan Office.